Community social capital and suicide mortality in the Netherlands: a cross-sectional registry-based study - Kunst, Anton E (BioMed Central, 2013)
BACKGROUND: Evidence on the effect of community social capital on suicide mortality rates is fragmentary and inconsistent. The present study aims to determine whether geographic variations in suicide mortality across the Netherlands were associated with community social capital. METHODS: We included 3507 neighbourhoods with 6207 suicide deaths in the period 1995–2000. For each neighbourhood, we measured perceived social capital using information from interview surveys, and we measured structural aspects of social capital using population registers. Associations with mortality were determined using Poisson regression analysis with control for confounders at individual level (age, sex, marital status, country of origin) and area level (area income, population density, religious orientation). RESULTS: Suicide mortality rates were related to the measure of perceived social capital. Mortality rates were 8 percent higher (95% confidence interval (CI): 2 to 16 percent) in areas with low capital. In stratified analyses, this difference was found to be significantly larger among men (12 percent, CI: 2 to 22) than women (1 percent, CI: -9 to 13), larger among those age 0–50 (18 percent, CI: 8 to 29) than older residents (−2 percent, CI: -12 to 8), and larger among the unmarried (30 percent, CI: 16–45) than the married (−2 percent, CI: -12 to 9). Associations with the structural aspect of social capital were in the same direction, but weaker, and not statistically significant. CONCLUSIONS: This study contributed some evidence to assume a modest effect of community social capital on suicide mortality rates. This effect may be restricted to specific population groups such as younger unmarried men.